Personal Identity and the Order of Principles in Leibniz’s Nouveaux Essais - Gutiérrez García, José Antonio; Sánchez Rodríguez, Manuel (Anales del Seminario de Historia de la Filosofía, 2026)
The aim of this paper is to analyze Leibniz’s metaphysical theory of personal identity and to engage with the debate initiated by Margaret D. Wilson, whose interpretation has significantly shaped contemporary scholarship. According to her reading, Leibniz would incur an inconsistency by simultaneously maintaining that we are immaterial substances and that a personal identity without substantiality would be possible. This article argues that such an interpretation rests on a misunderstanding of Leibniz’s sources. To this end, the two allegedly inconsistent theses are examined through an exposition of Locke’s theory of personal identity and of Leibniz’s response to it. In conclusion, it is argued that Leibniz’s concessions to Locke must be understood as rhetorical rather than systematic commitments: to admit the mere logical possibility of an apparent identity without substance does not amount to acknowledging its metaphysical possibility, since this would imply denying the rational order of the world, grounded in the principles of rationality.